THE USE OF VISUAL PROGRAMMING TOOLS IN TEACHING PROGRAMMING IN HIGH SCHOOL - Casagranda, Monique (2025)
This study aims to analyze the role of visual programming tools in teaching programming to high school students, focusing on how these technologies can improve student’s conceptual understanding, academic performance, and engagement. To achieve this, a bibliographic review of specialized literature on the subject was conducted, encompassing publications from 2019 to 2024, to explore the use of emerging technologies and interactive platforms such as Scratch, Tynker, and MIT App Inventor. The research indicates that these tools play an important role in facilitating the learning of complex programming concepts, promoting the development of computational thinking and problem-solving skills in a practical and visual way. Furthermore, it was found that the use of active methodologies, such as Project-Based Learning and Gamification, contributes to student engagement, making the learning process more accessible, dynamic, and tailored to individual needs. However, the study also identifies significant challenges, such as the lack of adequate technological infrastructure in schools and the need for ongoing teacher training to effectively integrate these tools into their pedagogical practices. The study concludes that while emerging technologies have the potential to transform programming education, a joint effort between educational institutions and governments is essential to invest in infrastructure and teacher training, ensuring that the benefits of these tools can be fully realized in the school environment.